Orientalism and the Exhibitionary Order - Mitchell, Timothy (Jama’a: an Interdisciplinary Journal of Middle East Studies, 1999)
This article explores the relationship between modern apparati of representation (such as exhibitions) and the construction, by the colonial order, of the non-Western other. The construction of the other was among the pillars of the colonial discourse. The article reconstructs the encounter of Arabs who had visited nineteenth century France with European representations of their own otherness. The article thus provides US with original insights into the various dimensions of invention related to the colonial representation of the world as an exhibition and into the relationship between forms of organizing knowledge and colonial domination. The Orientalist discourse is also explored through an examination of reports left by nineteenth-century European travelers to the Middle East. Thus, by tracing the ways in which Easterners and Westerners observed each other, the article points to the fluidity of the boundaries between reality and its representations.